Parametric investigation of heat transfer and fluid flow on laser micro-welding - Hozoorbakhsh, Asghar (2015)
The aim of this research is to investigate heat transfer and fluid flow phenomena during laser micro-welding of thin stainless steel sheet. A transient 3-D model is developed using computational fluid dynamics (CFD) method to understand some critical characterisation such as temperature fields and melt pool formation and also the perform parameters on laser micro-welding process. The applications of developed thermal models have demonstrated that the laser parameters, such as laser power,scanning velocity and spot diameter have considerable effect on the peak temperature and resulted weld pool. The heat source model is consisted of surface heat source and adaptive volumetric heat source that could be well represented the real laser welding as the heat penetrates into the material. In the computation of melt dynamics, mass conservation, momentum and energy equations have been considered to count the effects of melt flow and the thermo-fluid energy heat transfer. The three-dimensional governing equations from the Navier-Stokes for Newtonian fluid are used to estimate the melt flow that influences the rate of heat transfer and the distribution of temperature in a 3-D domain. Melt penetration is produced by the use of high power density distribution that results in rapid evaporation, which is expected to generate recoil pressure in the weld pool. Assuming that atmospheric and vaporised material pressure are balanced at the front of the laser beam, the evaporation of the melt leads to significant pressure that drills down the melt to the opposite side of the base material when it is heated over the boiling point. Furthermore, the surface tension of the molten material is also highly responsible for widening the melt pool. The melt surface layer is often influenced by contractive forces of the molten material to minimize its surface free energy. Minimization of the energy has a substantial effect on the melt surface to stretch out its extent towards the non-melted solid region. The simulation results have been compared with two sets of experimental research to predict the weld bead geometry and solidification pattern which laser welds are made on stainless steel (SUS304). The shape comparison describes those parameters relevant to any changes in the melt dynamics and temperatures are of great importance in the formation of weld pool and heat distribution during laser micro-welding. The fair agreement between simulated and experimental results has been achieved.